2012
DOI: 10.1128/iai.00060-12
|View full text |Cite|
|
Sign up to set email alerts
|

Mannose-Capped Lipoarabinomannan from Mycobacterium tuberculosis Induces Soluble Tumor Necrosis Factor Receptor Production through Tumor Necrosis Factor Alpha-Converting Enzyme Activation

Abstract: c Primary Mycobacterium tuberculosis infection results in granuloma formation in lung tissue. A granuloma encapsulates mycobacterium-containing cells, thereby preventing dissemination and further infection. Tumor necrosis factor alpha (TNF-␣) is a host-protective cytokine during M. tuberculosis infection due to its role in promoting and sustaining granuloma formation. TNF activity is regulated through the production of soluble TNF receptors (sTNFRI and sTNFRII). Therefore, we examined the potential production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…One possible explanation is that LAM suppresses the production of TNF-a during Mtb infection through production of TNF-receptor as a mechanism to reduce circulating TNF-a level (30). TNF-a is a potent inducer of apoptosis of infected macrophages, thereby facilitating cell-mediated immunity (31).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that LAM suppresses the production of TNF-a during Mtb infection through production of TNF-receptor as a mechanism to reduce circulating TNF-a level (30). TNF-a is a potent inducer of apoptosis of infected macrophages, thereby facilitating cell-mediated immunity (31).…”
Section: Discussionmentioning
confidence: 99%
“… 33 Previous studies have shown that excessive TNF-α levels cause damage to the immune pathological response in cells and to protection of the body’s defense. 34 36 TNF-α levels may be related to the severity of the disease process and may serve as a parameter for predicting the prognosis of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, one report indicates that ManLAM can promote extracellular release of soluble TNF-α receptor. Thus, ManLAM might also interfere with the extrinsic apoptosis pathway by neutralizing TNF-α (Richmond et al, 2012 ).…”
Section: Manipulation Of Phagocytes Responsesmentioning
confidence: 99%